CFD study on the hydrodynamics of fluidized granular activated carbon in AnFMBR applications - Cahyadi, Andy (2017)
The anaerobic fluidized bed membrane bioreactor (AnFMBR) utilizes the fluidization of granular activated carbon (GAC) particles as an unsteady-state shear means for mitigating membrane fouling. In this study, a two-fluid model (TFM) was validated against experimental results and used to obtain a comprehensive landscape of local water and particle velocities and concentrations throughout the reactor. The results provided interesting insights. Firstly, both water and particle velocities tended to be non-uniform vertically and laterally, which indicate that the extent of fouling across the membrane would be non-uniform. Secondly, to attain the same water shear stress or particle momentum values, the power required was greater for the larger particles, which indicate that smaller particles were more energy-efficient. Thirdly, at the same power input, the water shear stress or particle momentum values for the different particle diameters overlapped, which indicates that other parameters can be manipulated to improve performance even when particle diameter has been fixed. Fourthly, generally negative correlations existed between fouling rate and the hydrodynamics of both phases, but fouling rate and power input were poorly correlated, which suggests surprisingly that increasing power would not improve the fouling mitigation.